Life of Pi: Exploring functions of Pi16+ fibroblasts [version 1; peer review: 2 approved] - Yein Chung; Matthew B. Buechler; Erika E. McCartney (F1000Research, 2024)
Fibroblasts are mesenchymal cells that are responsible for creating and maintaining tissue architecture through the production of extracellular matrix. These cells also play critical roles in processes such as wound repair and immune modulation in normal tissues and various disease states including fibrosis, autoimmunity, and cancer. Fibroblasts have a complex repertoire of functions that vary by organ, inflammatory state, and the developmental stage of an organism. How fibroblasts manage so many functions in such a context-dependent manner represents a gap in our understanding of these cells. One possibility is that a tissue-resident precursor cell state exists that provides the fibroblast lineage with flexibility during growth, inflammation, or other contexts that require dynamic tissue changes. Recent work has suggested that a precursor fibroblast cell state is marked by expression of Peptidase inhibitor 16 (Pi16). This review aims to concatenate and compare studies on fibroblasts that express Pi16 to clarify the roles of this cell state in fibroblast lineage development and other functions.